1981
DOI: 10.1002/j.2050-0416.1981.tb04048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Non-Volatile Constituents of Wine by Glass Capillary Gas Chromatography*

Abstract: A considerable amount of quantitative and qualitative information on the non-volatile constituents of wine (acids, sugars, and polyols] can be readily obtained, from small sample volumes without prefractlonation, by glass capillary gas chromatography of their trimethylsilyl derivatives. A continuous check on the correct functioning of the method, and in particular on the inertness of the glass capillary and injector, is obtained by the use of two internal standards, whose trimethylsilyl derivatives vary consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The hydrolysis of sucrose would produce both glucose and fructose, but sucrose was not found in our wine samples even before malolactic fermentation (data not shown). Trehalose is another important wine disaccharide (32) whose hydrolysis would yield glucose. We did not specifically analyze this sugar, but some preliminary measurements indicated that its concentration decreased during malolactic fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of sucrose would produce both glucose and fructose, but sucrose was not found in our wine samples even before malolactic fermentation (data not shown). Trehalose is another important wine disaccharide (32) whose hydrolysis would yield glucose. We did not specifically analyze this sugar, but some preliminary measurements indicated that its concentration decreased during malolactic fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1990, the International Organisation of Vine and Wine (OIV) has issued specific official isotopic methods (OIV MA-AS-311-05 and MA-AS-312-06) to fight against this practice [7]. They are based on the analysis of the stable isotopic ratios of hydrogen (D/H) and carbon ( 13 C/ 12 C, expressed as δ 13 C) in ethanol distilled after fermentation. These two parameters are completely different depending on whether the ethanol comes from grapes or from exogenous sugars such as beets and cane, due to the different photosynthetic cycles (C3 or C4) of the plants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Myoand scyllo-inositol are two minor sugars characteristic of grape must [10][11][12], which are not retained by the resins used for the concentration process used to obtain CM and RCM, and these two polyalcohols are not naturally present in other commercial sugar syrups from different botanical origins (e.g., sucrose from beet, cane or sugar syrup from fruits, etc.). Furthermore, scylloand myo-inositol have been described as stable in terms of the storage or processing of juice [13].…”
Section: Introductionmentioning
confidence: 99%